2002
DOI: 10.1046/j.1365-2141.2002.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

Very low frequencies of human normal CD34+ haematopoietic progenitor cells express the Wilms' tumour gene WT1 at levels similar to those in leukaemia cells

Abstract: Summary. The Wilms' tumour gene, WT1, is expressed at high levels in leukaemia cells and plays an important role in leukaemogenesis. WT1 is also expressed in human normal CD34 + bone marrow (BM) cells at about 100 times lower levels than in leukaemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 51 publications
4
66
0
2
Order By: Relevance
“…As to the WT1 mRNA of the stem cell fraction, Hosen et al 31 described the very low frequency of normal CD34-positivehematopoietic progenitor cells with WT1 mRNA level similar to those in leukemia cells. Our current study supports their results.…”
Section: Gata-mentioning
confidence: 99%
“…As to the WT1 mRNA of the stem cell fraction, Hosen et al 31 described the very low frequency of normal CD34-positivehematopoietic progenitor cells with WT1 mRNA level similar to those in leukemia cells. Our current study supports their results.…”
Section: Gata-mentioning
confidence: 99%
“…[20][21][22] Except for very early investigations, 4 WT1 expression has been identified in normal BM and PSC controls or CD34 þ concentrates in all further studies, either in a proportion 25,37,39,42 or all 30,43,44 of the samples tested. In agreement with the latter studies, we could detect WT1 expression in all analyzed normal BM and PSC samples.…”
Section: Wilms' Tumor Gene 1 (Wt1) Expression L Boublikova Et Almentioning
confidence: 99%
“…Hematopoietic precursors show transient biphasic WT1 overexpression, which has a stage-specific effect: WT1 maintains primitive stem cells in a quiescent state, while it promotes differentiation of more mature lineage-committed progenitors. [20][21][22] Alterations of WT1 expression (both under-or overexpression) have been described in a number of malignancies and premalignant syndromes. Remarkably, WT1 overexpression has been found in 80-90% of acute myeloid leukemia (AML) and 70-90% of acute lymphoblastic leukemia (ALL) patients, with an even higher frequency at relapse.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that only 1.2% of normal human CD34 þ hematopoietic progenitor cells express WT1, and both CD34 þ CD38 À and CD34 þ CD38 þ bone marrow (BM) cells contain WT1-expressing cells at similar frequencies. 20 However, it remains to be determined what specific subsets of cells express WT1 in normal hematopoietic cells and leukemia cells.…”
Section: Introductionmentioning
confidence: 99%